The current state of spirituality: A four world view - Young, Taylor (Journal for the Study of Spirituality, 2025)
Though spirituality has become more prevalent in holistic Biopsychosocial-Spiritual (BPSS) health it is still scarcely acknowledged by the US healthcare system, its clinicians and along with it its systemic benefits. This article aims to provide a summarization of those benefits through Peek’s (2008) four world view (i.e. clinical, financial, operational, and training) of health care and discuss the lack of acknowledgment amongst these benefits. To better diversify the authors outlook on spirituality the modern clinical version of spirituality (Koenig 2008) was utilized as a clinical framework. The application of this framework is due in part to clinicians and their discomfort being one of the driving forces behind the lack of acknowledgment. Through this framework, clinicians can create a more welcoming stance for diverse spiritual presentations and increase acknowledgment of spirituality for their patients within the healthcare system. Due to this framework being conducive to a clinical stance it would benefit the acknowledgment of spirituality by beginning in the world of training. This stance would directly address clinician discomfort and increase the overall acknowledgment of spirituality. Improvements within the training world should be prioritized while also highlighting important conversations that should be happening simultaneously in the other three worlds (Table 1).